APLIKASI OPAC (ONLINE PUBLIC ACCESS CATALOG) PADA SISTEM INFORMASI PERPUSTAKAAN BERBASIS MOBILE - Fatsyahrina Fitriastuti (Fakultas Teknik dan Teknologi Informasi, Universitas Jenderal Achmad Yani Yogyakarta, 2011)
The development of the library world is supported by the development of information technology. Until now, there were some problems in the library world is trying to be approached by using information technology. With the advances in information technology now, especially seen from the development of programming languages, it is possible to do inter-library resource sharing or integration of library information systems in libraries located far apart. This integration combines the existing modules in each instance the acquisition or procurement system, pengkatalogan, circulation, catalog access by the public or known by the name of the OPAC (Online Public Access Catalog), and inter- library loan. Of all the modules or sub-system is the most important for the wearer is sub OPAC system, which memungkankan online access to the catalog so that it can be accessed by anyone and at any time without being limited by space and time. The resulting system will be accessible through the web either by personal computers (PCs), laptops, cell phones, or PDAs. Through this application user or member can browse your library perpustaakaan or search for books or other library collections needed and to know the location of the library where books are sought can be obtained by users. Application Online Public Access Catalog (OPAC)-based mobile can be accessed either via the internet online or through mobile phones is expected to overcome these kesulitasn. This system will facilitate access catalog of library collections such as searching by author, keyword, publisher, see a resume or abstract of the book, and obtain information in the library where books are located and the number ekslempar are still available. So that user can directly go to the TBM in accordance with the location obtained from the system.